UPAYA GURU PEMBIMBING MEMBANTU PESERTA DIDIK YANG MEMPEROLEH HASIL BELAJAR RENDAH DI KELAS VIII SMP N 1 PULAU PUNJUNG KABUPATEN DHARMASRAYA - Elya, Mona; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
Problem in this study is how the efforts of counselor help students who gain low learning outcong. This study alms to reveal: (1) an attempt totur helps learners im prove learning motivation, (2) guldance counselor attempts to help in improving the way of effective learning. This researchis a desviptive study that attempted to describe about a real situation. Population in this study were junior high school students grade VIII SMP N Pulau Punjung Kab. Dharmasraya there were 44 students. This sample taken from the population, therefor the sample collection technique is total random sampling. All population were sampled out come data were analyzed by using the tech nique of presentation. This study found that counselorâs effort to help students in improving motivation learning categorized unsatisfled because they onley get 52,3% and the datas also shows that supervisonâs efreetively also unsitisfleed that is 84,1%. The ralter suggest to superviser and all teacher in SMP N 1 Pulau Punjung Kab. Dharmasraya more foends to students who gor a problem in specially who get low scone study learning.